Days of Action or Restraint? How the Islamic Calendar Impacts Violence - REESE, MICHAEL J.; RUBY, KEVEN G.; PAPE, ROBERT A. (The American political science review, 2017)
Does the religious calendar promote or suppress political violence in Islamic societies? This study challenges the presumption that the predominant impact of the Islamic calendar is to increase violence, particularly during Ramadan. This study develops a new theory that predicts systematic suppression of violence on important Islamic holidays, those marked by public days off for dedicated celebration. We argue that militant actors anticipate societal disapproval of violence, predictably inducing restraint on these days. We assess our theory using innovative parallel analysis of multiple datasets and qualitative evidence from Islamic insurgencies in Iraq, Afghanistan, and Pakistan from 2004 to 2014. Consistent with our theory, we find that important Islamic holidays witness systematic declines in violence—as much as 41%—and provide evidence that anticipation of societal disapproval is producing these results. Significantly, we find no systematic evidence for surges of violence associated with any Islamic holiday, including Ramadan.